Shifting children's attentional focus to emotions during art museum experiences. (6th July 2021) - Korom, Marta; Callaghan, Bridget L.; VanTieghem, Michelle; Silvers, Jennifer A.; Choy, Tricia; Kalter, Jennifer; Blumenthal, Emily; Tottenham, Nim
Abstract : Art exposure can influence children's emotional growth, but little is known about tools that aid emotional development in art museums. We implemented attentional and social manipulations to test whether (1) modifications to unscripted instructions and (2) caregiver prompts shape children's attentional focus towards either the emotional or elemental content (e.g., colour and medium) of paintings. These manipulations occurred within an on‐going art museum education programme. Afterwards, children's ( N  = 60; ages 3–13 years) attentional focus towards emotions or elements was assessed by asking them to select words that best described the art. Children focused on emotion more, but the instructional manipulation successfully influenced word choices towards the targeted focus. Caregiver prompts also influenced focus towards the elements and away from emotions. These findings highlight that children's attention to art's emotional content can be altered by social context, which here was demonstrated within a museum programme.